2018
DOI: 10.1007/978-3-319-65798-1_22
|View full text |Cite
|
Sign up to set email alerts
|

Does the Variability of Evoked Tympanic Membrane Displacement Data (V m) Increase as the Magnitude of the Pulse Amplitude Increases?

Abstract: This study shows that large V variability is associated with a large spontaneous vascular pulse. This suggests that efforts to reduce vascular pulsing from recordings, either by a subtraction technique during post-processing or ECG-gating of the evoking stimulus, may improve reliability of the V measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…Although several studies have shown a significant relationship between evoked TMD and invasively obtained ICP [35,[48][49][50], several other studies noted high intersubject variability in the TMD measurements, questioning the clinical utility of TMD to measure ICP [35,49,[51][52][53]. However, a 2018 study by Sharif et al [52] suggested that some of the variability in TMD measurements may be related to an increased vascular pulse amplitude; a large pulse amplitude was associated with increased variability in evoked TMD. Therefore, accounting for the pulse amplitude may improve the reliability of the evoked TMD measurements.…”
Section: Tympanic Membrane Displacementmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have shown a significant relationship between evoked TMD and invasively obtained ICP [35,[48][49][50], several other studies noted high intersubject variability in the TMD measurements, questioning the clinical utility of TMD to measure ICP [35,49,[51][52][53]. However, a 2018 study by Sharif et al [52] suggested that some of the variability in TMD measurements may be related to an increased vascular pulse amplitude; a large pulse amplitude was associated with increased variability in evoked TMD. Therefore, accounting for the pulse amplitude may improve the reliability of the evoked TMD measurements.…”
Section: Tympanic Membrane Displacementmentioning
confidence: 99%
“…Although a 'corrected' evoked TMD may be a reliable indicator of ICP status, further studies are necessary to determine if a 'corrected' evoked TMD better correlates with invasively obtained ICP measurements than uncorrected evoked TMD. Currently, TMD is not widely used clinically as a noninvasive method to detect or monitor ICP due to large intersubject variability and prior reports of a variable correlation with invasively obtained ICP [48,51,52,54].…”
Section: Tympanic Membrane Displacementmentioning
confidence: 99%
“…TMD can be thought of as “evoked” or “spontaneous”, where evoked TMD is defined as the mean TM volume displacement, and spontaneous TMD is the time-dependent TM movement waveform 22 . However, several studies suggested that there is large inter-subject variability in the evoked TMD measurements, which has made it difficult to implement as a noninvasive method for ICP monitoring 23 , 24 . On the other hand, studies suggested that ICP oscillations can be transmitted to the tympanic membrane and spontaneous TMD waveform 19 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies suggested that there is large inter-subject variability in the evoked TMD measurements, which has made it di cult to implement as a noninvasive method for ICP monitoring [23][24]. On the other hand, studies suggested that ICP oscillations can be e ciently transmitted to the tympanic membrane and spontaneous TMD waveform [19,22].…”
Section: Introductionmentioning
confidence: 99%